IMPLEMENTASI METODE HUNGARIAN DALAM PENUGASAN KARYAWAN PADA PT. RIA SUKSES MANDIRI MEDAN - Zandroto, Tetty Natalia (JURIKOM (Jurnal Riset Komputer), 2019)
Assignment of employees in an office is a complicated matter and often has difficulty in the division of tasks which causes instability in the performance of employees. Employee assignment simulation in writing this essay was made to help the company. Applications using POM QM For Windows make the process of assigning employees very easy to get results as efficiently as possible. This resulted in the need for optimal assignment arrangements for the company. This employee assignment problem is solved by creating an employee assignment optimization model by maximizing the efficiency level of the use of POM QM For Windows software to minimize the level of employee dissatisfaction with the applicable tasks. The purpose of this study is to find the maximum value of employee assignments that will be applied by PT Ria Sukses Mandiri Medan. In searching for the maximized value the method used is the Hungarian algorithm. After doing the results of calculations using the Hungarian method, the company should implement this method in order to be able to place the employees to be worked on.